UMP volunteers continue to provide assistance for flood victims - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 25 December 2021 - More than 500 volunteers comprising staff and students from Universiti Malaysia Pahang (UMP) have been caring for flood victims in the state since the extreme flood event last week.